Cocaine- and amphetamine-regulated transcript (CART) peptide-positive neuron populations in the enteric nervous system of the porcine descending colon depend on age and gender - Makowska, Krystyna; Fagundes, Kainã R.C. [UNESP]; de Britto Mari, Renata [UNESP]; Gonkowski, Sławomir (Public Library of Science (PLoS), 2025)
The enteric nervous system (ENS) is a complex structure located in the wall of the gastrointestinal tract. One of the less-known active substances found in the ENS is cocaine- and amphetamine-regulated transcript peptide (CART). It is known that CART-positive enteric neurons take part in the reactions to pathological stimuli, but knowledge of physiological stimuli-dependent changes in their population is extremely limited. The aim of the present study was to investigate the age- and gender-dependent diversities in the distribution of CART-positive neurons in the porcine colonic ENS using the double immunofluorescence technique. The obtained results have shown that age affects the number of CART-positive neurons in the colonic ENS and the character and intensity of age-caused changes depend on the type of the enteric plexus, and the most visible changes have been noted in the myenteric plexus in which the percentage of CART-positive neurons amounted to 22.3 ± 0.2% in young females, 20.7 ± 0.4% in young males, 23.7 ± 0.2% in adult females and 25.8 ± 01% in adult males. Moreover, during the present study, sex-dependent diversities in the percentage of CART-positive neurons were found, especially in adult animals. The obtained results suggest that CART in the ENS takes part in neuroplasticity processes occurring during the development, maturation and/or aging of the gastrointestinal tract, as well as that the number of CART-positive neurons is controlled by sex hormones and depends on the gender. However, the elucidation of all aspects connected with the influence of age and gender on the population of CART-positive neurons in the ENS requires further comprehensive studies.